2001
DOI: 10.1021/es002052u
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Land Use on Water Quality of a Diverse New England Watershed

Abstract: Analysis of variations in major ion chemistry in the Mill River watershed reveals the importance of anthropogenic activities in controlling streamwater chemistry. Average concentrations of NO3- and SO4(2-) show a positive correlation with percent catchment area altered by human land uses, and concentrations of Cl- increase with road density. Water removal from municipal reservoirs increases the downstream concentration of NO3- and SO4(2-) over that predicted by land use changes, showing that removal of high qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 23 publications
0
71
0
10
Order By: Relevance
“…concentrations of NaCl in water at higher temperature and lower precipitation, i.e., higher temperature/precipitation ratio, as occurs in summer [42]. Indeed, as discussed above for EC, evaporation processes occurring during summer involve a decrease in surface water flow and then an increase in salt concentration in water.…”
Section: Trace Metal Concentration and Removal Efficiencymentioning
confidence: 88%
See 1 more Smart Citation
“…concentrations of NaCl in water at higher temperature and lower precipitation, i.e., higher temperature/precipitation ratio, as occurs in summer [42]. Indeed, as discussed above for EC, evaporation processes occurring during summer involve a decrease in surface water flow and then an increase in salt concentration in water.…”
Section: Trace Metal Concentration and Removal Efficiencymentioning
confidence: 88%
“…However, data from the present study showed a clear increase of NaCl concentration in summer. The temporal pattern of NaCl concentration is linked to climatic conditions: the highest concentrations of NaCl in water at higher temperature and lower precipitation, i.e., higher temperature/precipitation ratio, as occurs in summer [42]. Indeed, as discussed above for EC, evaporation processes occurring during summer involve a decrease in surface water flow and then an increase in salt concentration in water.…”
Section: Nacl Concentration and Removal Efficiencymentioning
confidence: 95%
“…In the New England Watershed, a positive correlation was found between the percentage of the catchment area altered by human activities and the concentration of chlorine (Rhodes et al, 2001). Agricultural irrigation and industrial cooling require the least in terms of water quality.…”
Section: Land Cover and Land Uses Of The Catchment Areasmentioning
confidence: 97%
“…These uses have in some cases conflicting water quality demands (Chapman, 1992). The increases in population and industrialisation have increased the range of requirements for water together with a greater demand on higher quality water (Chapman, 1992; Rhodes et al, 2001). But due to low levels of industrialisation in Africa, changes in water quality of lakes does not present the same problem as in highly industialised countries (Kitaka et al, 2002).…”
Section: Land Cover and Land Uses Of The Catchment Areasmentioning
confidence: 99%
“…Ini dibuktikan oleh Tu (2009) yang menilai kesan gabungan perubahan iklim dan aktiviti guna tanah terhadap kualiti sumber air di kawasan tadahan air di Timur Massachusetts. Kajian yang sama turut dilakukan oleh penyelidik lain dengan mengaitkan kesan gabungan ini terhadap kualiti sumber air contohnya aliran air semasa musim kering dan basah (Gasim et al 2006), permukaan tanah (Rhodes et al 2001), pelepasan loji rawatan air sisa (Ferguson et al 1996), pembajaan pertanian (Mattikalli & Richards 1996) serta landskap dan persekitaran (Lee et al 2009). Menyedari hakikat ini, tindakan pemeliharaan serta pemuliharaan segera perlu dilakukan bagi mengelak pencemaran berterusan sehingga mengganggu sumber air sedia ada (Pingale et al 2014).…”
Section: Pengenalanunclassified